Determinants of celebrity endorsement towards consumer buying behavior / Qhairun Izzati Ruslan - Ruslan, Qhairun (Faculty of Business and Management, 2018)
This research explores on factors contributes on consumer buying behavior in Faculty Media and Communication student in Universiti Teknologi MARA Kampus Alor Gajah Melaka. This research also determined the factors consumer buying behavior at Faculty Media and Communication student in Universiti Teknologi MARA Kampus Alor Gajah Melaka, as well as to examine the factors of physical attractiveness, credibility congruence and expertise has significant relationship with consumer buying behavior and also want to signify which factor is the most influence towards consumer buying behavior and lastly to make a recommendations to improve it. To achieve this objective, a survey has been conducted among Media and Communication student in Universiti Teknologi MARA Kampus Alor Gajah Melaka and total of 127 forms of questionnaires were made to deliver among the Media and Communication student in Universiti Teknologi MARA Kampus Alor Gajah Melaka. The findings indicate that there is a significant positive relationship between expertise towards consumer buying behavior. It was also found that physical attractiveness, credibility and congruence does not has a significant positive relationship towards consumer buying behavior. On the other hand, expertise is the variable that influence the most towards consumer buying behavior and also there are recommendations for the companies that are suggested by researcher to improve the choices of the celebrity endoser.